(untitled) (Journal of Enam Medical College, 2019)
Odontomas are benign tumours of odontogenic origin consisting of different dental tissues. Usually they are tooth size or smaller, but occasionally complex variety can exhibit considerable growth. They are usually asymptomatic and often are discovered during routine radiograph. Morphologically odontoma can be classified as complex when present as irregular masses containing different types of dental tissues, or as compound if there is superficial anatomic similarity to even rudimentary teeth known as denticles. We report a case of large complex odontoma that causes pain, infection and facial asymmetry. J Enam Med Col 2019; 9(1): 57-59